Acceptability of low molecular weight heparin thromboprophylaxis for inpatients receiving palliative care: qualitative study. Issue 7541 (3rd February 2006) - Noble, S I R; Nelson, A; Turner, C; Finlay, I G
Abstract: Objective To find out what inpatients with advanced cancer who are receiving palliative care think about the effect of thromoprophylaxis on overall quality of life. Design Qualitative study using audiotaping of semistructured interviews. Setting Regional cancer centre in Wales. Participants 28 inpatients with advanced metastatic cancer receiving palliative care and low molecular weight heparin. Main outcome measures Recurring themes on the effect of thromboprophylaxis on overall quality of life. Results Major emerging themes showed that patients knew about the risks of venous thromboembolism and the purpose of treatment with heparin. Media coverage had raised awareness about venous thromboembolism, and many had previous experience of thromboprophylaxis. All found low molecular weight heparin an acceptable intervention, and many said that it improved their quality of life by giving them a feeling of safety and reassurance. Antiembolic stockings were considered uncomfortable and had a negative impact on quality of life. Patients were concerned that because they had advanced disease they might not be eligible for thromboprophylaxis. Conclusion Low molecular weight heparin is acceptable to inpatients with advanced cancer receiving palliative care and has a positive impact on overall quality of life. Antiembolic stockings are an unacceptable intervention in this patient group. Guidelines on thromboprophylaxis are urgently needed for palliative care inpatient units and hospices.